Changes in attitudes of mental health care staff surrounding the implementation of peer support work: A qualitative study. - Guillermo Ruiz-Pérez; Madeleine Küsel; Sebastian von Peter (PLoS ONE)
Background The integration of Peer Support Workers (PSWs) in mental health settings may encounter resistance due to the attitudes of Mental Health Workers (MHWs). At the same time, PSWs may initiate changes in the attitudes, as well as in the larger institutional culture. This paper addresses the question of which changes happen and how they occur. Methods This work is part of the ImpPeer-Psy5 study, funded by the German Innovation Fund, which examines the nationwide implementation of PSWs in health insurance-funded mental health care. Data were derived from two qualitative sub-studies: QUAL1encompassed 57 problem-centered interviews conducted with PSWs, MHWs working together with PSWs, and service users; QUAL2 consisted of one focus group and five interviews only with MHWs. Qualitative data were analyzed using a modified thematic analysis adapted to a collaborative research approach. Results The main findings included that working with PSWs makes MHWs better integrate lived experience insights into their caregiving, pay more attention to life contexts, advance towards a more appreciative language, use diagnostic categories more flexibly, and show more openness towards their own affectedness. These changes are reported to be mediated by the simple presence of PSWs, their "role model" function for other staff, or more direct forms of feedback and critique. Conclusion Overall, staff attitudes changed as a result of reflexive processes induced by their interactions with PSWs. This poses a dilemma as changes in MHWs and larger institutions are expected to occur prior to the implementation of peer support work to facilitate their integration. Further research is needed to evaluate whether and how staff training can facilitate the implementation of PSWs by targeting MHWs' attitudes.